English Course Program in Karang Indah Village, Mandastana District - Salsabila, Ariesta Ayu; Putra, Muhammad Adhitya Hidayat; Triyono, Sigit; Nur’aini, Fatwa; Syarifuddin, Syarifuddin (Journal of Social Development, 2024)
Currently, students still have relatively low English proficiency. This causes the improvement of English skills to be done to obtain maximum results. One of them is the English Course Program in Karang Indah Village, Mandastana District. Karang Indah Village as the location for the implementation of the English Course Program makes it specific compared to other villages in Barito Kuala Regency. Research Objective: To describe the English Course Program in Karang Indah Village, Mandastana District. This study uses a qualitative approach with a descriptive method. The collection techniques in this study are Observation, Interview, and Documentation. The instruments in this study are the researcher himself assisted by interview guidelines, recording tools, and stationery. The data analysis techniques in this study are in the form of data reduction, data presentation and conclusion drawn. Test the validity of the data used by credibility tests, transferability tests, and dependability. Research results: In its implementation, the English Course Program in Karang Indah Village, Mandastana District has several stages, namely the planning stage and the implementation stage of learning activities. The planning stage includes: tutor/teacher training, course participant registration, cost plan, learning location, learning plan. Meanwhile, the stage of implementing learning activities includes: making learning implementation plans, learning materials, learning media, learning methods, and assessment of learning activities. The existence of the English Course Program in Karang Indah Village is expected to improve the quality of human resources through English language skills.